Sociological Analysis of the Comparison of Social Dimensions of Employment in Two Vulnerable Groups (Female Heads of Households and Individuals with Disabilities) - Nargesi Khoramabad, Nasrin; Shiri, Tahmures; Mohseni, Reza Ali (Psychology of Woman Journal, 2024)
Objective: This study aims to conduct a sociological examination comparing the social dimensions of employment in two vulnerable groups: female heads of households and individuals with disabilities. Methods and Materials: The present research is applied in terms of its objective and has been conducted using a quantitative survey method. Data were collected through a researcher-made questionnaire, which was utilized after confirming its validity and reliability. The statistical population included beneficiaries under the nationwide welfare organization, with a sample population consisting of 384 individuals with disabilities and 384 female heads of households under the welfare organization’s coverage. Respondents were selected based on random sampling. Data analysis was performed using SPSS software. Findings: The results from the Mann-Whitney U test indicated that overall, there is no significant difference between the employment of female heads of households and individuals with disabilities (U = 68402.500, p = 0.083) in terms of social dimensions. This means that, from a social perspective, the two groups face similar challenges. Additionally, examining the social components of employment revealed significant differences between the two groups in the components of role performance, social support, individual/social rights, and employment barriers. However, in terms of the job security component (U = 70140.500, p = 0.238), there is no significant difference between these two vulnerable groups. Both groups, individuals with disabilities and female heads of households, lack job security. Conclusion: Attention to the social dimensions of employment for these two vulnerable groups by relevant organizations, especially in establishing job security for them, is essential and requires increased focus.